Rancang Bangun Pompa Hidram sebagai Solusi Sistem Pengairan di Daerah Perbukitan - Didik Firmana; Iqrima Staddal; Mustofa Mustofa (JTPG (Jurnal Teknologi Pertanian Gorontalo), 2022)
Water is one of the natural resources needed by all living things. Not only for human and animal consumption but water is also needed by plants for the process of growth and development. In areas where the position is low (below sea level), water is very easy and often found. However, in contrast to hilly and mountainous areas. Generally, farmers rely on rainwater to meet crop water needs. Therefore, hydram pump technology is a solution for irrigation systems in hilly and mountainous areas. This study aims to design a hydram pump system with a two-valve system. This research was conducted through several stages, namely design, provision of tools and materials, functional design and structural design, and testing. The main material for making hydram pumps comes from PVC pipes with different diameters, namely ¾, 2, and 3 inches. The design of the hydram pump consists of several main components, namely the input pipe, output pipe, delivery valve, waste valve, and air tube. Based on the results of the type 2 valve hydram pump test, the resulting discharge data is 8 liters/minute. The flow velocity in the input pipe and the output pipe are 0.052 m/s and 0.42 m/s respectively. One of these differences is influenced by the diameter of the pipe, where the flow velocity is inversely proportional to the diameter of the pipe. The flow rates generated in the input pipe and output pipes are 1.33 x 10‑4 m3/s and 1.32 x 10‑4 m3/s respectively.